1996
DOI: 10.1002/(sici)1099-0720(199606)10:3<225::aid-acp376>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Age and Skill Differences in the Processing Demands of Visual Inspection

Abstract: Two experiments investigated the effects of age and domain‐specific experience on the speed and accuracy of visual inspection performance. In Experiment 1, young (M age = 26.5 years) and middle‐aged (M age = 45.7 years) medical laboratory technologists (MTs) and matched novices were tested on a domain‐specific version and on a domain‐general version of a probe recognition task. Middle‐aged subjects were slower than younger subjects on both versions, and MTs were more accurate but slower than controls on the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A possible account for this may be the expertise that older adults developed through numerous years of driving. Studies examining performance on visual tasks have found that older experts are not disadvantaged relative to younger, less experienced individuals (Dollinger and Hoyer, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A possible account for this may be the expertise that older adults developed through numerous years of driving. Studies examining performance on visual tasks have found that older experts are not disadvantaged relative to younger, less experienced individuals (Dollinger and Hoyer, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Could training effects be synergistic in the former group but independent in the latter population? Dollinger and Hoyer (1996) report the results of two rigorous empirical studies, which show that middle-aged medical laboratory technicians use their domainspecific knowledge to help them perform exceptionally well on an occupationally related recognition task, yet these same technicians exhibit an age-related decrement in domain-general recognition. This suggests that older adults are capable of using a number of compensatory strategies in order to maintain their cognitive performance in everyday settings and that standard laboratory tasks may underestimate the functional/adaptive skills of the elderly.…”
mentioning
confidence: 99%